Antibiotics in orbital floor fractures. Issue 1 (1st January 2003) - Martin, Bruce; Ghosh, Angaj; Mackway-Jones, K
Abstract : A short cut review was carried out to establish whether prophylactic antibiotics are indicated in patients with undisplaced maxillary or orbital floor fractures. Altogether 214 papers were found using the reported search, but none presented any evidence to answer the clinical question. More research is needed in this area and, in the mean time, local advice should be followed.